The Dark Side of Science: Changing features in the Alliance between Science and Religion - Comstock, W Richard (Journal of Dharma, 1983)
In spite of the great differences between religion and science, there has been an alliance between the two that has helped to form what we call modern civilization. At the present time the ties that have bound the two together are becoming less secure. In this paper, I want to suggest some reasons why it is in fact desirable from the standpoint of religion not to take it for granted that religion and science have the same goals in common.